Antimicrobial effects of lysophosphatidylcholine on methicillin-resistant Staphylococcus aureus. (July 2017) - Miyazaki, Haruko; Midorikawa, Naoko; Fujimoto, Saki; Miyoshi, Natsumi; Yoshida, Hideto; Matsumoto, Tetsuya
Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) is an important health care-associated and community-associated pathogen and causes a large number of infections worldwide. For the purpose of application to topical treatment of MRSA infection, we examined the antimicrobial effects of lysophosphatidylcholine (LPC) on MRSA strains. We also investigated the combination effect of LPC and gentamicin on MRSA growth. Methods: The LPC minimum inhibitory concentrations (MIC) for Gram-positive ( S. aureus, Staphylococcus epidermidis, and Streptococcus pneumoniae ) and Gram-negative ( Escherichia coli, Enterobacter cloacae, Klebsiella pneumoniae, and Pseudomonas aeruginosa ) bacteria were measured by the broth microdilution method. The mechanism of LPC-mediated MRSA killing was investigated by membrane permeability analysis with DiSC3(5) fluorescence and growth curve analysis. Lastly, the effects of LPC on gentamicin-induced bactericidal activity were determined in combination treatment studies with 15 gentamicin-resistant MRSA isolates from the skin, nose, or ears. Results: The LPC MIC for Gram-positive bacteria varied between 32 µg/ml and >2048 µg/ml, whereas that for all Gram-negative bacteria was >2048 µg/ml. Consistently, membrane permeability analysis showed that LPC was substantially more effective in inducing membrane permeability in Gram-positive bacteria than in Gram-negative counterparts. Growth curve analysis in cotreatment studies demonstrated that LPC has intrinsic bactericidal effects and can also potentiate gentamicin sensitivity in resistant MRSA strains. Conclusions: Our study demonstrates that LPC exhibits intrinsic antimicrobial effects and can enhance the antimicrobial effects of gentamicin for resistant MRSA strains, suggesting that LPC may be a beneficial additive in topical antibiotics for superficial skin infections.